Adverse drug events and medication problems in "Hospital at Home" patients. Issue 3 (3rd July 2018) - Mann, Elizabeth; Zepeda, Orlando; Soones, Tacara; Federman, Alex; Leff, Bruce; Siu, Albert; Boockvar, Kenneth
ABSTRACT: "Hospital at Home(HaH)" programs provide an alternative to traditional hospitalization. However, the incidence of adverse drug events in these programs is unknown. This study describes adverse drug events and potential adverse drug events in a new HaH program. We examined the charts of the first 50 patients admitted. We found 45 potential adverse drug events and 14 adverse drug events from admission to 30 days after HaH discharge. None of the adverse drug events were severe. Some events, like problems with medication administration, may be unique to the hospital at home setting. Monitoring for adverse drug events is feasible and important for hospital at home programs.